The relationship between cognitive function and physical function in rheumatoid arthritis - Shin, So Young; Julian, Laura; Katz, Patricia (Journal of rheumatology, 2013)
To examine the relationship between cognitive impairment and functional limitations and disability in persons with rheumatoid arthritis (RA). Individuals from a longitudinal cohort study of RA participated in study visits that included physical, psychosocial, and biological metrics. Cognitive function was assessed using a battery of 12 standardized neuropsychological measures yielding 16 indices covering a range of cognitive domains. On each test, subjects were classified as "impaired" if they performed 1 SD below age-based population norms. Total cognitive function scores were calculated by summing the number of tests on which individuals were classified as "impaired" (higher scores = greater impairment). Performance-based and self-reported functional limitations were assessed with the Short Physical Performance Battery (SPPB) and the Health Assessment Questionnaire (HAQ), respectively. Self-reported disability was measured with the Valued Life Activities (VLA) scale. Multiple regression analyses controlling for sex, race, education, cardiovascular comorbidity, disease duration, disease severity, and depression were conducted to identify whether cognitive impairment was independently associated with physical function difficulties. There were 122 subjects with mean (SD) age of 58.4 (± 10.8) years; 62% were female and 80% were white. In multivariate regression models, total cognitive function score was significantly associated with greater functional limitations (SPPB: β = -0.24, p = 0.014; HAQ: β = 0.24, p = 0.003) but not with disability (VLA: β = 0.10, p = 0.207). Cognitive impairment was significantly associated with greater functional limitations in patients with RA, suggesting that cognitive impairment may play a role in poor functional status in persons with RA.